Inflammatory biomarker response to GLP-1 receptor agonists versus other glucose-lowering medications in patients with type 2 diabetes: a systematic review and meta-analysis - Alrasheed, Tariq; Mostafa, Mohamed E. A.; Madkhali, Mohammed A; Khairy, Hesham A (Frontiers in Endocrinology, 2026)
BackgroundType 2 diabetes (T2D) is strongly linked to chronic inflammation and oxidative stress, which drive cardiovascular complications. Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) demonstrate cardioprotective benefits that may extend beyond glycemic control, but their effects on key inflammatory and oxidative stress biomarkers compared to other glucose-lowering medications remain inconsistently reported across individual studies.MethodsA systematic review and meta-analysis of randomized controlled trials (RCTs) was conducted. Databases were searched for RCTs comparing GLP-1 RAs against other antidiabetic drugs or placebo in adults with T2D, reporting changes in inflammatory biomarkers (C-reactive protein [CRP], interleukin-6 [IL-6], tumor necrosis factor-alpha [TNF-α]) or the oxidative stress marker malondialdehyde (MDA). Data were pooled using a random-effects model, and outcomes were stratified by comparator type (placebo, insulin, other oral antidiabetic drugs [OADs]).ResultsForty RCTs (n=6029 participants) were included. GLP-1 RA therapy significantly reduced CRP levels compared to placebo (SMD = -0.59; 95% CI: -0.84 to -0.34) and other OADs (SMD = -1.06; 95% CI: -1.64 to -0.47). A significant reduction in TNF-α was observed versus placebo (SMD = -0.61; 95% CI: -0.89 to -0.32) and oral antidiabetic drugs add on (SMD = -1.62; 95% CI: -2.86 to -0.38). Data for MDA were limited and showed a non-significant trend toward reduction. GLP-1 RAs also significantly reduced IL-6 versus insulin (SMD = -0.24; 95% CI: -0.46 to -0.02). While significant heterogeneity was noted across the analyses, sensitivity analyses confirmed a consistent direction of effect, reinforcing the class-wide anti-inflammatory properties of GLP-1 RAs.ConclusionGLP-1 RAs significantly improve key biomarkers of systemic inflammation (CRP, TNF-α) in patients with T2D compared to various active comparators and placebo. These pleiotropic effects provide a mechanistic rationale for their cardiovascular benefits and support their use as a multifaceted therapeutic strategy in T2D management.